Perspektif Al-Qur'an tentang Hak dan Kewajiban Suami Istri sebagai Upaya Pencegahan Kekerasan dalam Rumah Tangga - Sapinah; Achmad Abubakar; Sohrah (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
This study aims to analyse the Qur'anic verses related to the rights and obligations of husband and wife, as well as explore ways to contextualise these verses in an effort to prevent domestic violence (KDRT) in the modern era. This research uses a qualitative approach with the type of library research. The data used is secondary data, which includes the Qur'an, Hadith, books, and articles relevant to the topic of discussion. The results of the analysis show that the Qur'an emphasises the principles of love (mawaddah wa rahmah), good treatment of spouses, equality in husband and wife relations, and responsibility as a family leader, which are the foundation for the creation of a harmonious household. These principles serve as a theological foundation in the prevention of domestic violence. A correct understanding of Qur'anic verses can be an effective solution to domestic violence, especially in highly religious societies such as Indonesia. This study recommends the education of Qur'anic values in premarital programmes, strengthening the role of religious institutions, and formulating policies based on Islamic principles as an effort to prevent domestic violence. This approach is expected to create harmonious families and a society free from violence in accordance with Qur'anic values.